Social Networks and Gender Violence at University Level in the XXI Century - Martínez Verdú, Remedios (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The core theme of this article is the issue of education and gender violence and social networks. The population group to be analysed is made up of young university students from the Bachelor's Degree in Education and Sociology at the University of Alicante, since this is a risk group when it comes to reproducing sexist behaviour and, furthermore, because education in egalitarian values can be fundamental in the prevention of gender violence. There are many variables to be taken into account in the phenomenon of gender violence, including age, which is also related to education.